Patent Search Tools for Competitive Intelligence for Product Design and Development of CBRN Decon Device - Sandal, Nidhi; Gupta, Prem Chand; Sharma, Rakesh Kumar; Sepat, Naval Kishore; Kumar, Avinash (DESIDOC Journal of Library & Information Technology, 2017)
Product design and development needs a lot of relevant and background information at the initial stage itself and literature review is one of the initial and important process in the new product design (NPD) process. In NPD, patent analysis is an important part of literature review, since the patent documents represent a huge reservoir of most systematic and updated information about any particular technology and product. A systematic search on a trusted global patent database with proper analytical tools could be used as powerful R&D tool to not only identify the state-of-art but also to extract leads to solution for critical R&D problems. Therefore, a focused search on professional patent database was performed to extract most relevant patent documents for R&D work related to the chemical, biological, radiological and nuclear (CBRN) decontamination device. Semantic keyword search and IPC based search followed by a thorough screening and analysis of the searched documents resulted in useful patent documents. These patent documents disclosed various aspects related to CBRN decontamination device which helped in the design & development of a novel CBRN Decon device.